Sampling plan for B-biotype of Bemisia tabaci in cucumber crop - Moura, Marcelo Fialho de; Picanço, Marcelo Coutinho; Silva, Ézio Marques da; Guedes, Raul Narciso Carvalho; Pereira, Jardel Lopes (Pesquisa Agropecuaria Brasileira, 2003)
The adoption of pest management integrated programs decreases insecticide applications, and standardized sampling plans represent the initial point in the generation of those programs. This work aimed to determine a conventional sampling plan for B-biotype of the whitefly Bemisia tabaci Genn. (Hemiptera: Aleyrodidae) in cucumber crops. The densities of nymphs and adults were evaluated in ten commercial crops in Tocantins, Minas Gerais State, Brazil. Nine sampling systems compared three sampling techniques, which were the beating of leaf on white plastic trays, the direct counting of insects on abaxial leaf surface, and the leaf collection in plastic bag, and three sample units, a leaf on the apical, median, and basal thirds of the training system. The system with the largest economic precision in the nymphs sampling was the direct counting on leaf of the basal third of the training system. However, that system did not generate a practicable sampling plan. The systems with the largest economic precisions in the adults’ sampling were the beating on plastic trays of a leaf from the apical, medium or basal portions of the training system. Only the sampling system of beating leaves of the third medium on plastic trays generated a practicable plan. The number of samples for the adults’ sampling on the leaves of the medium portion of the training system was of 196 per field.